2018
DOI: 10.1111/mec.14884
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular consequences of stepwise temperature increase across generations in a coral reef fish

Abstract: Global warming will have far‐reaching consequences for marine species over coming decades, yet the magnitude of these effects may depend on the rate of warming across generations. Recent experiments show coral reef fishes can compensate the metabolic challenges of elevated temperature when warm conditions are maintained across generations. However, the effects of a gradual temperature increase across generations remain unknown. In the present study, we analysed metabolic and molecular traits in the damselfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
66
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 77 publications
(119 reference statements)
13
66
2
Order By: Relevance
“…Unfortunately, obtaining a "control" year was logistically impossible because we could not predict the heatwave conditions sufficiently in advance, and due to an already very ambitious sampling scheme for species with no previous genomic resources (with the exception of A. polyacanthus). Despite these limitations, the functions of genes that showed expression changes over the duration of the heatwave concur with previous laboratory experiments on A. polyacanthus, one of the most studied tropical marine fish species in the context of global change (19,20).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Unfortunately, obtaining a "control" year was logistically impossible because we could not predict the heatwave conditions sufficiently in advance, and due to an already very ambitious sampling scheme for species with no previous genomic resources (with the exception of A. polyacanthus). Despite these limitations, the functions of genes that showed expression changes over the duration of the heatwave concur with previous laboratory experiments on A. polyacanthus, one of the most studied tropical marine fish species in the context of global change (19,20).…”
Section: Discussionsupporting
confidence: 83%
“…When temperatures are too high, the cardiorespiratory system is no longer able to fulfill additional oxygen demands for aerobic activities, leading to a reduction in aerobic performance (15,16), alteration of growth rates (17), and reduction in swimming speeds (18). Previous studies focusing on gene expression of captive fishes have shown that increased oxygen demands at higher temperatures can lead to activation of genes related to mitochondrial activity, the electron-transport chain, fatty acid metabolism, and cellular stress response (19,20). Furthermore, reproductive hormones can be affected by warmer conditions, leading to changes in reproductive behavior and declines in reproductive output (21).…”
Section: Introductionmentioning
confidence: 99%
“…After all, the genome and, more especially, its regulation must be highly dynamic to allow for plasticity to occur and we need to learn more about both genetic and epigenetic mechanisms to understand how climate stressors can influence and shape genomes, transcriptomes and the epigenome, in particular, across generations. In recent years, considerable effort has been expended on trying to understand the molecular, genomic and epigenomic mechanisms underlying responses to climate stressors across a variety of species and populations, including fish [72][73][74][75][76], corals [77,78], other invertebrates [79 -81] and plants (review: [82]). In the process, we have substantially increased our knowledge of the molecular mechanisms underlying plasticity (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…These included proteins related to the heat shock response (HSP), Abbreviations: CV, coefficients of variance; DDA, data-dependent acquisition; DIA, Data-independent acquisition. a well-documented expression change seen in fish exposed to elevated temperatures (Basu et al, 2002), cytochrome related genes involved in oxidative stress and several other previously identified stress response genes in marine fish representing protein degradation and cell death. In Figure 4, we see the combined DDA libraries provided the least identifications of the complex cellular stress response identified by the other libraries.…”
Section: Differential Expression and Functional Analysismentioning
confidence: 91%